1975
DOI: 10.1073/pnas.72.6.2260
|View full text |Cite
|
Sign up to set email alerts
|

Satellite-Rich DNA in Cucumber: Hormonal Enhancement of Synthesis and Subcellular Identification

Abstract: Cucumber hypocotyl DNA in neutral CsCl distributes into a mainband comprising 59% of the total, and two large satellite bands which contribute 41%to the DNA pattern. Organelle enrichment studies show that the densities of mitochondrial and chloroplast DNA coincide with those of the satellite bands. At least 12-19% of total cucumber DNA is associated with the cytoplasmic organelles. These In prior studies, gibberellin-induced elongation of the cucumber hypocotyl was correlated with an increased incorporatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

1976
1976
1987
1987

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…One of the hazards associated with isolation of satellite DNA by the CsCI density gradient method is the possibility of contamination with DNA derived from chloroplasts and mitochondria (Kadouri et al, 1975). Possibly, much of the DNA of Cucurbitaceae identified by some workers as satellite may be of this origin.…”
Section: Differentiation Of Nuclear Dna With Respect To Structure Andmentioning
confidence: 98%
“…One of the hazards associated with isolation of satellite DNA by the CsCI density gradient method is the possibility of contamination with DNA derived from chloroplasts and mitochondria (Kadouri et al, 1975). Possibly, much of the DNA of Cucurbitaceae identified by some workers as satellite may be of this origin.…”
Section: Differentiation Of Nuclear Dna With Respect To Structure Andmentioning
confidence: 98%
“…ii Uptake cpm~~~~~DNA cpm/mg DNA (19). The total DNA content of isolated aleurone layers does not increase during incubation, although thymidine is incorporated into DNA.…”
mentioning
confidence: 99%
“…The suggestion of Kadouri et aL (7) that the percentage of chloroplast DNA should be highest in plants with nuclei of low DNA content is probably correct, but their value of 12 to 19%o chloroplast DNA in cucumber does not agree with these results. The cucumber genome is not unusually small as suggested by Kadouri et aL (7). Also, not all plant species with small genomes have satellite DNA (e.g.…”
Section: Resultsmentioning
confidence: 70%
“…Recently it was suggested that a major component of certain satellite DNAs was organellar (3,7). This implied that the method commonly used for nuclear DNA preparation, the selective solubilization of organelles by treatment with Triton X-100 (10), was ineffective, and that chloroplast DNA constituted a much greater proportion of the total DNA than was previously supposed (11).…”
mentioning
confidence: 99%